Early Reading Difficulties among Young Twins: A Survey Study on Phonological Challenges and Cryptophasia in East Kalimantan - Pertiwi, Adharina Dian; Kartika, Wilda Isna; Maghfirah, Febry; Kamila, Karina Cahya; Fortuna, Safira Bunga Cinta; Setianingsih, Hesti Putri; Ferdiyanti, Tiara (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2025)
One of the receptive language abilities that must be developed in early childhood before progressing to more advanced stages is the capacity for early reading. Language development in twins tends to be slower compared to that of children in general. Difficulties commonly observed include challenges in word pronunciation and verbal reading. Cryptophasia is a unique phenomenon in the language development of twins; crypto'' means secret, and phasia'' refers to a speech disorder. The purpose of this research is to collect data from a representative sample to draw broader conclusions about early reading abilities in twins. This survey-based study employs a quantitative methodology, focusing on 66 twins in Samarinda. Data were collected using a research instrument checklist comprising nine basic items. Each item is scored on a scale from zero to five. Survey results, with a maximum score of one, reveal the following average abilities: recognizing vowel letters (3.64); recognizing consonant letters (2.71); spelling consonant-vowel patterns (1.68); spelling open syllables V-C-V (1.70); spelling identical open syllables C-V-C-V (1.68); spelling varied open syllables C-V-C-V (1.67); spelling closed syllables C-V-C-V-C (1.59); spelling syllables with diphthongs (1.59); and spelling syllables with double consonants (1.47). The overall average early reading ability score among young twins is 1.85. The findings indicate that the reading ability of twins is lower than that of children in general. Strong vowel recognition and moderate consonant recognition serve as the foundation for reading development. However, the low ability to spell syllables highlights the need for targeted intervention, particularly due to the influence of cryptophasia. Although this study was conducted in Kalimantan Timur, it offers valuable insights into early reading abilities in twins. Future research is recommended to further explore twin language development in diverse contexts.